INFORMATION RESOURCES EFFECT ON THE QUALITY COMPARATIVE ANALYSIS OF THE MECHANISM OF STATE-PRIVATE PARTNERSHIP IN THE DEVELOPMENT OF TRANSPORT INFRASTRUCTURE - T. Bogdanova (Вестник университета)
In the article, authors considered value of information resource as bases of high-quality comparison of public-private partnership at development of transport infrastructure at different social and economic stages of development of Russia. On concrete examples, comparison of use of the mechanism of public-private partnership in the sphere of transport is carried out. The comparative analysis of pre-revolutionary and modern experience of public-private partnership made by authors of article in the sphere of transport showed expediency of use of a method of analogies at assessment of transport projects.